The modernist God state : a literary study of the Nazis' Christian Reich - Lackey, Michael (Continuum International Pub., 2012)
The Modernist God State seeks to overturn the traditional secularization approach to intellectual and political history and to replace it with a fuller understanding of the religious basis of modernist political movements. Lackey demonstrates that Christianity, instead of fading after the Enlightenment, actually increased its power by becoming embedded within the concept of what was considered the legitimate nation state, thus determining the political agendas of prominent political leaders from King Leopold II to Hitler. Lackey first argues that novelists can represent intellectual and politi.